Pesantren: Sebuah Realitas Pendidikan Multikultural - Bukhori, Imam (LP3M Universitas Islam Zainul Hasan Genggong, 2017)
Boarding school is an educational institution that is not looking at the social strata and is a religious institution that is synonymous with tafaqquh fid-din to stay on track with its cultural, religious education with the goal that the transfer of knowledge and the transfer of moral and social servitude sincerely. Model that applied by pesantren in education multicultural among the students and mostly depend on the ideas and insights kiai about Islam that is inclusive, moderation, tolerance and harmony to bring the school and his students obtained Islam friendly and rahmatan lil'alamin the cultures that developed around schools. Multicultural education is not specifically granted in the form of subjects or special studies, but through a variety of opportunities and activities in schools.